Fatigue Detection Using Decision Tree Method based on PPG signal - Ilham Ari Elbaith Zaeni; Arya Kusuma Wardhana; Erianto Fanani (JURNAL INFOTEL, 2023)
Fatigue is a complex psychophysiological condition marked by sleepiness or fatigue, poor performance, and a range of physiological changes. A decision tree may be used to categorize weariness based on the subject's heart rate data. To begin the experiment, a dataset of the heart rate signal was obtained. The signal has already undergone preprocessing. The feature obtained through preprocessing is then used to construct the decision model. Four traits were discovered. The HF power, LF power, normalized HF power, and normalized LF power are the characteristics. This research has a 75.94% accuracy rating. The precision, recall, and F-measure scores for this study were 0.736, 0.736, and 0.736, respectively.